I win it's fair, you win it's not: Selective heeding of merit in ambiguous settings - Serhiy Kandul; Olexandr Nikolaychuk (Friedrich Schiller University Jena, 2021)
One's willingness to accept an outcome or even to correct it depends on whether or not the underlying procedure is deemed legitimate. We manipulate the role allocation procedure in the dictator game to illustrate that this belief is not independent of the outcome and is self-serving in its nature. Our findings suggest that there may be some positive level of dissatisfaction with virtually any social outcome in the populace without there being anything wrong as far as the underlying procedure. We also discuss the perceptions of fairness and merit as potential drivers of the observed behavioral phenomenon.
Keywords: D63; D91; 330; fairness; entitlement; merit; redistribution; procedural preferences; dictator game